Multi-omics analysis the differences of VOCs terpenoid synthesis pathway in maintaining obligate mutualism between Ficus hirta Vahl and its pollinators - Fan, Songle; Jia, Yongxia; Wang, Rong; Chen, Xiaoyong; Liu, Wanzhen; Yu, Hui (Frontiers in Plant Science, 2022)
Volatile organic compounds (VOCs) emitted by the receptive syconia of Ficus species is a key trait to attract their obligate pollinating fig wasps. Ficus hirta Vahl is a dioecious shrub, which is pollinated by a highly specialized symbiotic pollinator in southern China. Terpenoids are the main components of VOCs in F. hirta and play ecological roles in pollinator attraction, allelopathy, and plant defense. However, it remains unclear that what molecular mechanism difference in terpenoid synthesis pathways between pre-receptive stage (A-phase) and receptive stage (B-phase) of F. hirta syconia. Transcriptome, proteome and Gas Chromatography-Mass Spectrometer (GC-MS) were applied here to analyze these difference. Compared to A-phase syconia, the genes related to the terpenoid synthesis pathway had higher expression level in receptive syconia (B-phase) according to transcriptome sequencing. Seven differentially expressed transcription factors were screened, namely bHLH7, MYB1R1, PRE6, AIL1, RF2b, ANT, VRN1. Specifically, bHLH7 was only specifically expressed in B-phase. 235 differentially expressed proteins (DEPs) were mainly located in the cytoplasm and chloroplasts. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DEPs were mainly enriched in the metabolic process. A total of 9 terpenoid synthesis proteins were identified in the proteome. Among them, 4 proteins in methylerythritol phosphate (MEP) pathway were all down-regulated. Results suggested the synthesis of terpenoids precursors in B-phase bracts were mainly accomplished through the mevalonic acid (MVA) pathway in cytoplasm. Correlation analysis between the transcriptome and proteome, we detected a total of 1082 transcripts/proteins, three of which are related to stress. From the VOCs analysis, the average percent of monoterpenoids emitted by A-phase and B-phase syconia were 8.29% and 37.08%, while those of sesquiterpenes were 88.43% and 55.02% respectively. Monoterpenes (camphene, myrcene, camphor, menthol) were only detected in VOCs of B-phase syconia. To attract pollinators, B-phase syconia of F. hirta need more monoterpenoids and less sesquiterpenes. We speculate that transcription factor bHLH7 may regulate the terpenoid synthesis pathway between A- and B-phase syconia. Our research provided the first global analysis of mechanism differences of terpenoid synthesis pathways between A and B phases in F. hirta syconia.